ANALISIS PENGGUNAAN MEDIA POHON LITERASI PADA PEMBELAJARAN BAHASA INDONESIA KELAS II - arlina, arlina; Narayanti, Putu Satya; Kertayasa, I Ketut (JATMIKA : Journal Education and Learning of Elementary School, 2025)
The study aims 1) to analyze the teacher's perception of the tree's media usage on Indonesian learning, 2) to analyze students' perceptions of the tree's media use to English study, 3) to analyze the underlying factors and the tree's media barrier to English learning. Sampling an informer with an impressive. sample. Methods used: observation, interview, documentation, and angket. The object of this study is the process of using the literacy tree media at class ii school at bk school Tipo Kelurahan. Research indicates that teachers are helped in increasing student involvement and understanding, and students state that this use of the literal literal literal tree makes learning more interesting and easier to understand the material. This is based on student response ratings, 64% of the lowest and 100% highest scores for an "yes" answer on the use of tree media in Indonesian studies. Contributing factors in the use of numeric tree media are the teacher's educational background and work experience that make teachers adept at using learning media, enthusiastic students, and comfortable classrooms. The inhibitors to the use of the literal literal tree media, the lack of sufficient time or hours of study, the cost limitations and parents who undersupport student educational needs.